Distribution of Hypothalamic Neurons with Orexin (Hypocretin) or Melanin Concentrating Hormone (MCH) Immunoreactivity and Multisynaptic Connections with Diaphragm Motoneurons - Badami, Varun M. (2010)
Prior work showed that neurons in the lateral, dorsal, and perifornical regions of the tuberal and mammillary levels of the hypothalamus participate in the control of breathing. The same areas also contain large numbers of neurons that produce either orexins (hypocretins) or melanin concentrating hormone (MCH). These peptides have been implicated in regulating energy balance and physiological changes that occur in transitions between sleep and wakefulness, amongst other functions. The goal of this study was to determine if hypothalamic neurons involved in respiratory control, which were identified in cats by the retrograde transneuronal transport of rabies virus from the diaphragm, were immunopositive for either orexin-A or MCH. In animals with limited rabies infection of the hypothalamus (< 10 infected cells/section), where the neurons with the most direct influences on diaphragm motoneurons were presumably labeled, a large fraction (28–75%) of the infected hypothalamic neurons contained orexin-A. In the same cases, 6–33% of rabies-infected hypothalamic cells contained MCH. However, in animals with more extensive infection, where rabies had presumably passed transneuronally through more synapses, the fraction of infected cells that contained orexin-A was lower. The findings from these experiments thus support the notion that hypothalamic influences on breathing are substantially mediated through orexins or MCH.